Perspectives of Antidiabetic Drugs in Diabetes With Coronavirus Infections - Sun, Bao; Huang, Shiqiong; Zhou, Jiecan (Frontiers in Pharmacology, 2021)
Diabetes mellitus (DM) increases the risk of viral infections especially during period of poor glycemic controls. Emerging evidence has reported that DM is one of the most common comorbidities in the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) infection, also referred to as COVID-19. Moreover, the management and therapy are complex for individuals with diabetes who are acutely unwell with suspected or confirmed COVID-19. Here, we review the role of antidiabetic agents, mainly including insulin, metformin, pioglitazone, sulfonylureas, dipeptidyl peptidase-4 inhibitors, sodium-glucose cotransporter 2 inhibitors and glucagon-like peptide 1 receptor agonists in DM patients with coronavirus infection, aiming to address the clinical therapeutic choices for these subjects.